VANETs Multipath Video Data Streaming Considering Road Features - Aliyu, Ahmed; Abdullah, Abdul Hanan; Budiyono, Avon; Raja Mohd Radzi, Raja Zahilah; Mohammed Joda, Usman (International Journal of Integrated Engineering, 2018)
Multipath video streaming in Vehicular Ad-hoc Networks (VANETs) is an evolving research topic. The adoption of video transmission in VANETs communication has become essential due to the comprehensiveness and applicability of video data for on-road advertisement and infotainment. Meanwhile, several research studies have considered how to apply and improve the transmission of the video quality. Due to this, the concurrent multipath transmission has been employed in order to achieve load balancing and path diversity, because of the high data rate of the video data.Â  However, the main nature of the road, which is the pathway for VANET nodes has not been considered explicitly. In this paper, the road features are considered for VANETs multipath video streaming based on the greedy geographical routing protocol. Thus, VANETs Multipath Video Streaming based on Road Features (VMVS-RF) protocol has been proposed. The protocol was compared with an ordinary Multipath Video Streaming (MVS). The result demonstrates that the proposed VMVS-RF protocol outperforms the MVS in terms of Data Receiving Rate (DRR), Structural Similarity (SSIM) index and Packet Loss Ratio (PLR).